1976
DOI: 10.1159/000465540
|View full text |Cite
|
Sign up to set email alerts
|

Groups of a-D- Galactosyltransferase Activity in Sera of Individuals with Normal B Phenotype

Abstract: In the Paris population of blood donors with normal B phenotype, two groups can be formed owing to their respective serum a-D-galactosyltransferase activity and red cell aggiutinability with an anti-B antibody. Both parameters are closely correlated. The aggiutinability groups partially overlap. In an African population from various ethnical origins, this correlation was observed only in some individuals. 11 among 20 subjects belonged to a third group defined by a high transferase activity. The third group wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1977
1977
1978
1978

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…Besides, enzyme activities of Aj and A2 subjects overlap widely. The large range of enzyme activities observed among Aj individuals do not seem to be related to the existence of distinct groups of transferase activities, similar to those described by Badet et al [1] for the a-D-galactosyltransferases detected in the sera of subjects of blood group B.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Besides, enzyme activities of Aj and A2 subjects overlap widely. The large range of enzyme activities observed among Aj individuals do not seem to be related to the existence of distinct groups of transferase activities, similar to those described by Badet et al [1] for the a-D-galactosyltransferases detected in the sera of subjects of blood group B.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, the a-Dgalactosyl transferase activity of AmB individuals sera tested according to a technique described elsewhere [1] was found to be normal. However, one Am sample (HOE.…”
Section: Measurements Of Glycosyltransferase Activities On 2'fl Studymentioning
confidence: 89%
“…18 hr incubation process with 2'FL. The amount of A or B [14C]tetra~accharide* synthesized after 18 hr of incubation at 37°C by 10 p1 of A or B human sera in the presence of 2'FL in standard conditions of assay has already been described (Badet et al, 1974;Cartron et al, 1975). 72 hr incubation process with 2'FL or human H substance.…”
Section: A and B Blood Group Glycosyltransferase Assays In Seramentioning
confidence: 99%
“…Ident8cation of reaction products. Following the incubation process of 18 to 72 hr, the A and/or B tetrasaccharides synthesized from 2'FL were isolated and identified as previously described (Badet et al, 1974;Cartron et al, 1975). The N-acetyl-~-[-l-~~C]galactosamine incorporated onto the H substance was estimated after high voltage electrophoresis in 0.1 M ammonium formate buffer, pH 3-5 (Whatman paper No.…”
Section: A and B Blood Group Glycosyltransferase Assays In Seramentioning
confidence: 99%
“…Badet et al [1] report great variation in transferase activity, and ascribe observed discrepancies between transferase activity and red cell agglutinability to the indepen dent action of B and H genes, resulting in variation of the red cell antigens. They further suggest that combinations of dif ferent transferase activities may give rise to observed differences between racial groups.…”
Section: Resultsmentioning
confidence: 99%